Visual coverage of the 2006 Lebanon War: Framing conflict in three US news magazines. (April 2015) - Schwalbe, Carol B; Dougherty, Shannon M
The 2006 Lebanon War presented a rare opportunity to explore how the three major US news magazines visually covered a distant conflict in which the US was not directly involved. Time, Newsweek, and U.S. News & World Report faced the challenge of how to fairly report a conflict that was dominated by one side – Israel. A quantitative content analysis revealed that the military conflict and human interest frames dominated visual coverage of the seven-week war. By emphasizing the war's negative impact on Lebanon and its people, the news magazines provided a largely American audience with a proportional visual representation of the conflict. Only 11 percent of the images showed the injured and dead, which is consistent with other war studies. This article discusses how the news magazines visually framed the war, why images of Hezbollah and protests were rarely seen, and why many casualty images included women and children.